Venetoclax in combination with hypomethylating agents or low dose cytarabine for relapsed and refractory acute myeloid leukemia. Issue 7 (7th June 2022) - Graveno, Molly E.; Carulli, Alison; Freyer, Craig W.; Mangan, Brendan L.; Nietupski, Robert; Loren, Alison W.; Frey, Noelle V.; Porter, David L.; Gill, Saar I.; Hexner, Elizabeth O.; Luger, Selina M.; Martin, Mary Ellen; et al.
Abstract: Limited treatment options exist for patients with relapsed/refractory (R/R) acute myeloid leukemia (AML). Venetoclax (VEN) in combination with a hypomethylating agent (HMA) or low-dose cytarabine (LDAC) has been recently approved for treatment-naïve patients unfit for intensive induction. Limited data are available to characterize the efficacy of VEN combinations in R/R AML. We retrospectively analyzed 77 patients with a median of 1 prior therapy (range 0–5) treated with VEN combinations for R/R AML or AML secondary to myelodysplastic syndrome (MDS) progressing after HMA monotherapy. The median overall survival (OS) was 13.1 months (95% CI 9.2–15.1). The median progression-free survival (PFS) was 12 months (95% CI 8.2–15.4) with a median duration of response of 8.9 months (95% CI 5.7–13.9). Overall response rate (ORR) was 68% with a composite complete response (CR) and CR with incomplete hematologic recovery (CRi) rate of 53%. VEN combination therapy is efficacious in R/R AML and further prospective studies are warranted.